A circularly polarized wideband high gain patch antenna for wireless power transfer. Issue 3 (5th February 2018) - Di Carlo, C. A.; Di Donato, L.; Mauro, G. S.; La Rosa, R.; Livreri, P.; Sorbello, G.
Abstract: This article deals with a microstrip patch antenna working at 868 MHz, suitable for the radio frequency wireless power transfer and energy harvesting applications. The proposed monolithic antenna is compact, lightweight and it is printed on a thick substrate in order to maximize the total gain in the broadside direction. The antenna radiates at 868 MHz with a fractional impedance bandwidth of 5% and it shows a gain of 4.14 dB.